(Com) vivendo com drogas de abuso : percepção social em uma comunidade do Noroeste do Paraná - Reis, Lúcia Margarete dos (2012)
Given the negative effects of abusive drugs in family life and in communities, and the importance of public policy actions addressed to the needs of communities, the aim of the study was to analyze the social perception on the presence of abusive drugs and violence in a community from the Paraná Northeast. This is a cross-sectional, quantitative and descriptive research, using population-based household survey. Data were collected through structured questionnaire, adapted from the assessment instrument of the Social Perception Indicator System, and applied to a random sample of 358 residents of a community that has high indicators of violence related to the use of abusive drugs.Data were analyzed through Statistical Analysis Software (SAS), being subjected to the simple descriptive analysis and Binomial Proportion Test. Interviewees had an average age of 44.1 ± 14.9 years, the majority were women (68.2%), white race/color (57.5%) and 36.3% had between nine and 11 years of schooling. The average family income per capitaamounted to R$ 534, 12.9% had no paid occupation and 5.6% developed autonomous activity as a source of income. Of the 244 interviewed women, 29.9% reported being housewives. The average length of residence in the community was 14.3 years and only five (1.4%) of interviewees reported not knowing the use of abusive drugs in the community. Drug use was found in 18.2% of respondents and 19.8% reported having drug use in the family, being that crack use was referred by 2.5%. The majority (82.4%) considered that drugs are present in high intensity; such a situation is regarded as 'disturbing' to 56.1% and cause of suffering to 61.5% of respondents. 260 respondents (72.6%) reported having restrictions in their daily activities for fear of suffering violent acts. The main reason for the circulation and consumption of abusive drugs in the community was related to the lack of policing (31.4%). The majority (90.2%) perceives the presence of violence in the community and has related it to use of abusive drugs. Only 13.9% of respondents perceive the presence of actions to prevent the use and to combat the drug trafficking and violence in the community. The presence of abusive drugs (24.9%), poor health care (20.9%) and public safety (13.7%) were the most relevant problems in the community, and increase the policing (55.3%) was reported as the most essential action to combat the use of abusive drugs and eliminate violence in the community. Three phenomena were relevant: the number of unemployed women or who reported staying at households; the high perception about the presence of abusive drugs in the community, and the evidence of an expansion culture of the use of abusive drugs in the household, with the inclusion of the crack in the family scope. Although the presented analysis refers to data that identifies just a fraction of the problems associated with drug use, it provides important information on relevant aspects of the phenomenon and unequivocally reflects the severity, breadth and magnitude of these problems in our country and our communities.